Revisiting the Determinants of Child Anthropometric Indicators in India Using Seemingly Unrelated Regressions Model. Issue 3 (December 2016) - Naline, G.; Viswanathan, Brinda
This study uses the National Family Health Survey (NFHS-3) data to estimate Seemingly Unrelated Regression (SUR) model for height-for-age (HAZ), weight-for-age (WAZ) and weight-for-height (WHZ) to understand how the determinants of intergenerational transmission, feeding and care practices, and the Integrated Child Development Scheme (ICDS) vary in their impact when these commonly used measures of child nutritional status are considered together in a systems framework. As expected mother's height, BMI and anaemia levels are all highly important in explaining the variations with large impact of height on HAZ, of BMI on WAZ and of anaemia on WHZ. Initiation of breastfeeding within an hour of child's birth, exclusive breastfeeding in the first six months and inclusion of protein rich diets for the older children has a large impact on HAZ, and so does access of daily food supplements from the ICDS by rural children. Other predictors such as wealth status, safe water access, sanitation and use of clean cooking fuel by the households are found to be strongly associated with all the indicators. The results from this study strengthen the evidence that though multiple determinants play a role in a child's growth, the key factors are in the mother to child transmission and in quality of early child care of feeding habits and preventive and curative health care practices.